2015
DOI: 10.22502/jlmc.v3i2.66
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic Bacteriuria in Diabetic Adults

Abstract: Introduction: Urinary Tract Infection (UTI) is a well- known complication of Diabetes Mellitus (DM). Its spectrum ranges from Asymptomatic Bacteriuria (ABU) to acute pyelonephritis. Many studies have delineated an increased prevalence of ABU in DM whereas to the same degree other studies have come to naught showing insignificant association. Hence, this study was drafted to evaluate the presence of ABU among diabetics and assess various risk factors.   Methods: Total of 116 diabetic adults without … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 15 publications
(18 reference statements)
2
3
1
Order By: Relevance
“…The prevalence of ASB among elderly diabeticswas 9.8% and 4.6% in non diabetics. This result was very similar with the study done by BK Jha et al (9.43%), 18.4% in study done by Manish Rijal et al and 10.3% by A. Adhikari et al [7][8][9] Butin some study prevalence of ASB in diabetic patients was comparatively higher. 10,11 The most common microorganisms in this study was Escherichia coli, 53.8% in diabetics 66% in non diabetics followed by Klebsiella, pseudomonas, staphylococcus, coagulase negative staphylococcus.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The prevalence of ASB among elderly diabeticswas 9.8% and 4.6% in non diabetics. This result was very similar with the study done by BK Jha et al (9.43%), 18.4% in study done by Manish Rijal et al and 10.3% by A. Adhikari et al [7][8][9] Butin some study prevalence of ASB in diabetic patients was comparatively higher. 10,11 The most common microorganisms in this study was Escherichia coli, 53.8% in diabetics 66% in non diabetics followed by Klebsiella, pseudomonas, staphylococcus, coagulase negative staphylococcus.…”
Section: Discussionsupporting
confidence: 90%
“…Among 11 Gram negative bacteria only 1 was resistant to Imipenem that was pseudomonas isolated from the urine sample of diabetic patients, age 72 with the mean HbA1c levels significantly higher and was multidrug resitant. Nitrofurantoin was the sensitive antibiotics after the Imepenem, against the urinary isolates similar pattern was also reported in a study of Manish Rijal et al 9 Most isolated microorganisms were resistant to Amoxyclav and Norfloxacin. Gram positive bacteria were sensitive to Vancomycin and Teicoplanin.…”
Section: Discussionsupporting
confidence: 85%
“…Ajay Adhikaree et al in their study included 116 diabetic adults and observed that overall prevalence of ASB was 10.3% and patients with poor glycemic control had higher prevalence of ASB in comparison to those with good glycemic control. [ 10 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 6 ] In another study conducted by Adhikaree et al , E. coli was the most frequently isolated pathogen (75%), followed by Klebsiella (16.7%) and Staphylococcus aureus . [ 10 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation